Hydroxyurea for the Treatment of Sickle Cell Disease: Efficacy, Barriers, Toxicity, and Management in Children - Strouse, John J. (2012)
Hydroxyurea is the only approved medication in the United States for the treatment of sickle cell anemia (HbSS) and is widely used in children despite an indication limited to adults. We review the evidence of efficacy and safety in children with reference to pivotal adult studies. This evidence and expert opinion form the basis for recommended guidelines for the use of hydroxyurea in children including indications, dosing, therapeutic and safety monitoring, and interventions to improve adherence. However, there are substantial gaps in our knowledge to be addressed by on-going and planned studies in children.